Advances in accounting education teaching and curriculum innovations. Vol. 5 - Ketz, J. Edward; Schwartz, Bill N. (Advances in accounting education : teaching and curriculum innovations,, 2003)
Advances in Accounting Education is a refereed, academic research annual whose purpose is to meet the needs of individuals interested in ways to improve their classroom instruction. Articles may be either empirical or non-empirical and emphasize pedagogy, explaining how teaching methods or curricula/programmes can be improved.